In the Lap of the Buddha: Intimacy in Tibetan Ritual - Cameron David Warner (Religions)
Following the re-opening of the Rasa Trulnang Tsuklhakhang, the central temple in Lhasa, all of the new images of Buddhas, bodhisattvas, and famous lamas were placed behind glass except for those in the sancta sanctorum, the “Jokhang”. When a pilgrim approaches the central figure, the Jowo Śākyamuni, she climbs a ladder on his right side, lays a ceremonial scarf across his lap, and then lays her head there, like a child seeking solace from her mother. A wealthy pilgrim might return in the late afternoon, when the temple is closed to visitors, to sponsor a regilding ceremony, in which the sponsor can spend up to an hour nearly alone with the Jowo watching his whole body be repainted in gold. Based on participant observation, pilgrimage guides, and verses of praise offered to the Jowo, this paper considers how the cult of the Jowo uses moments of private intimacy to bridge the distance, both physically and historically, between a devotee and the Buddha.